La Equidad De Género En Los Agronegocios: Sector Comercio De Insumos Agropecuarios Y Servicios Veterinarios Del Cantón Machala - Prado-Carpio, Eveligh; Castro-Armijos, Cristhian Jover; Castillo-Herrera, Sara; Quezada-Abad, Cesar; Coronel-Reyes, Julián; Arias-Chiriboga, Héctor (European Scientific Journal, ESJ, 2018)
One of the most important global challenges is the eradication of gender inequality, an indicator that is constantly evaluated, and for which the countries of the world have developed public policies aimed at increasing the levels of equity in the population. The present investigation was carried out in the city of Machala, and for which it was proposed as an objective to establish the participation of women and men in agribusiness in the trade sector of agricultural inputs and veterinary services and their characteristics and as hypotheses that in the agribusiness in the sector of agricultural inputs and veterinary services, there is a great gender inequity, which is sought to scale; for its realization was taken the information of the national cadastre of agribusiness registered in Agrocalidad in the sector of agricultural inputs and veterinary services, which are a total of 75, of these, 35 were surveyed to determine the degree of equity and participation of the woman; the variables analyzed were the university academic degree of the local owners, the age and the reason to undertake. The data were analyzed using the chi-square test and using the statistical program SPSS 20. The results obtained demonstrate the low participation of women in this economic sector of the city of Machala.